Fe on molecular-layer MoS2 as inorganic Fe-S-2-Mo motifs for light-driven nitrogen fixation to ammonia at elevated temperatures - Zheng, J; Lu, L; Lebedev, K; Wu, S; Zhao, P; McPherson, IJ; Wu, T-S; Kato, R; Li, Y; Ho, P-L; Li, G; Bai, L; et al. (Cell Press, 2021)
Current industrial production of ammonia from the Haber-Bosch process and its transport concomitantly produces a large quantity of CO2. Herein, we successfully synthesize inorganic-structure-based catalysts with [Fe-S2-Mo] motifs with a connecting structure similar to that of FeMoco (a cofactor of nitrogenase) by placing iron atoms on a single molecular layer of MoS2 at various loadings. This type of new catalytic material functionally mimics the nitrogenase to convert N2 to ammonia and hydrogen in water without adding any sacrificial agent under visible-light illumination. Using the elevated temperature boosts the ammonia yield and the energy efficiency by one order of magnitude. The solar-to-NH3 energy-conversion efficiency can be up to 0.24% at 270°C, which is the highest efficiency among all reported photocatalytic systems. This method of ammonia production and the photocatalytic materials may open up an exciting possibility for the decentralization of ammonia production for fertilizer provision to local farmlands using solar illumination.